PERAN PIMPINAN DALAM MENINGKATKAN MOTIVASI DAN KINERJA KARYAWAN TVRI STASIUN JAKARTA - Ayu Nitria; Joned Ceilendra Saksana; T Ramli Zakaria (Jurnal Ilmiah Ekonomi, Manajemen dan Bisnis, 2020)
Leadership is a pivotal element in elevating the performance of any organization from its basic to peak levels, presenting a powerful force that propels organizational success. This study explores the role of leadership in enhancing employee motivation and performance at TVRI Station Jakarta, highlighting the originality of focusing on media industry leadership dynamics. Employing a qualitative survey method, this research collects data through observations, interviews, and documentation to delve into these leadership impacts. Analysis techniques include data presentation, reduction, and the drawing of conclusions. Results indicate that leadership at TVRI Station Jakarta significantly enhances employee motivation and performance through guidance, fun, comfort, appreciation, and training. These findings suggest that implementing strategic leadership practices can substantially benefit employee engagement and performance in the broadcasting sector. The study contributes to the theoretical and practical understanding of leadership’s effect on motivation and performance, offering insights applicable to similar settings in the media industry